CFTR mutations in three Latin American countries (2000)
We analyzed 192 cystic fibrosis (CF) alleles in three Latin American countries: Mexico, Colombia, and Venezuela. Mutation screening was performed by polymerase chain reaction (PCR) and a reverse dot blot detection kit that enables determination of 16 of the most common CF mutations worldwide. Mutations were detected in 47.9% of the screened CF alleles. The most prevalent CF allele was ?F508 (39.6%). The remaining 16 non-?F508 detectable mutations represented 8.3% of the CF alleles. Among them, the G542X, N1303K, and 3849+10kb C > T were the most common. Although the frequency of ?F508 described here is lower than that reported for Caucasian populations, including in Spain, it is remarkable that mutation prevalences found in this study resemble those observed in Spain. Two of these mutations, G542X and 3849+10kb C>T, that were relevant in this analysis, have a particularly high incidence in Spanish communities. The low frequency of ?F508 described here may be explained by the Amerindian, Caucasian, and Black admixture that occurred in Latin America after the discovery of the New World, and also by the probable occurrence of mutations contributed by the original natives, which were undetectable in this analysis. (C) 2000 Wiley- Liss, Inc.